Ekstraksi Serat Alam Untuk Aplikasi Material Komposit Dengan Mesin Dekortikator - Nanang Endriatno; La Ode Ahmad Barata (Piston: Jurnal Teknologi, 2024)
Natural fibers have advantages compared to synthetic fibers because they are biodegradable and sustainable. The problem with natural fibers is the extraction or separation process of the skin and fiber. This research aims to design a decorticator that separates leather and natural fibers to be used as composite reinforcing materials. The procedure for creating a decorticator machine is carried out by collecting initial data and requirements about the decorticator machine, determining effective decorticator machine technology and mechanisms, designing concepts and mechanisms, and planning detailed drawings. From this research, a decorticator design was created with a frame component that functions as the primary support for the machine components; the beater shaft functions to scrape the stem by moving quickly and breaks the outer layer of the stem so that the fibers can be separated, the rolling cylinder functions to hold the fiber during the process of separating the fiber and stem, the machine cover functions to provide safety during operation, the petrol motor as the driving force, and the pulley-belt transmission system. Apart from separating fiber from non-fiber parts, decorticator machines can also increase the use of environmentally friendly natural fibers as composite materials and reduce dependence on synthetic materials.